Capacity driven small cell deployment in heterogeneous cellular networks: Outage probability and rate coverage analysis. Issue 6 (6th February 2020) - Ullah, Arif; Haq Abbas, Ziaul; Muhammad, Fazal; Abbas, Ghulam; Jiao, Lei
Abstract: Heterogeneous cellular networks (HCNets) are one of the key enabling technologies to improve performance gain of future cellular networks. Stochastic geometry is considered a promising tool to model and analyze HCNets. Users and base stations (BSs) are generally distributed uniformly using a homogeneous Poisson point process (HPPP). The assumption of uniformly distributed users is not suitable in HCNets because of the existence of clustered users in hotspots. To consider the correlation between the users and BSs, deployment of small base stations in these areas are of great concern to increase the performance of HCNets. In this article, we assume the notion of mixed user distribution, wherein the network users are the superposition of clustered and uniform users, modeled through HPPP and Poisson cluster process, respectively. We evaluate outage probability and rate coverage of the proposed HCNet model. We compare the network performance of the proposed mixed user distribution model with the conventional uniformly distributed user model. The analytical results are validated using Monte‐Carlo simulations. Our results show that the proposed HCNet model of mixed user distribution outperforms the uniformly distributed user model in terms of outage probability and rate coverage. Abstract : A two‐tier HCNet model: MBSs (represented by squares) and SBSs (represented by diamonds) are distributed according to two independent HPPPs. Dash‐dotted lines and circles represent the coverage area of MBSs and SBSs, respectively. A mixed user distribution (uniform users plus clustered users) is used with dots representing clustered users around SBSs and stars representing uniformly distributed users. HCNet, heterogeneous cellular network; HPPPs, homogeneous Poisson point process; MBSs, macro base stations; SBSs, small base stations